Psychometric properties of a Spanish version of the Beck - Sanz, Jesús; Magán, Inés; García-vera, María Paz (The Spanish Journal of Psychology, 2008)
This is the first study that provides normative, reliability, factor validity and discriminant validity data of the Beck Anxiety Inventory (BAI; Beck, Epstein, Brown, & Steer, 1988) in the Spanish general population. Sanz and Navarro’s (2003) Spanish version of the BAI was administered to 249 adults. Factor analyses suggested that the BAI taps a general anxiety dimension comprising two related factors (somatic and affective-cognitive symptoms), but these factors hardly explained any additional variance and, therefore, little information is lost in considering only full-scale scores. Internal consistency estimate for the BAI was high (= .93). The BAI was correlated .63 with the BDI-II and .32 with the Trait Anger scale of the STAXI 2, but a factor analysis of their items revealed three factors, suggesting that the correlations between the instruments may be better accounted for by relationships between anxiety, depression, and anger, than by problems of discriminant validity. The mean BAI total score and the distribution of BAI scores were similar to those found in other countries. BAI norm scores for the community sample were provided from the total sample and from the male and female subsamples, as females scored higher than males. The utility of these scores for assessing clinical significance of treatment outcomes for anxiety is discussed.